2021
DOI: 10.1016/j.jsps.2021.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Role of pharmacist during COVID-19 pandemic: A retrospective study focused on critically ill COVID-19 patients

Abstract: Background and aim During the Coronavirus 2019 (COVID-19) crisis, there has been a huge demand for medications and unprecedented utilization of intensive care unit (ICU) services that subsequently and profoundly impacted the quality of medical care provided to COVID-19 patients. This study aimed to shed light on the role of pharmacists on the health care provided to critically ill COVID-19 patients. Methods A retrospective study, was conducted in Diriyah hospital in Riy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…This is in line with published literature suggesting that hypertension is a risk factor for Covid-19 morbidity and mortality [34][35][36][37]. Again, in a pharmacists' intervention study in Saudi Arabia [26], hypertension and diabetes were the most prevalent comorbidities which were diagnosed in 59.5% and 58% of the patients respectively, quite higher compared to 35% and 18.7% obtained in our study. Other pharmacists' intervention studies also showed hypertension, diabetes, and renal impairment as most prevalent in a Covid-19 ward [38].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is in line with published literature suggesting that hypertension is a risk factor for Covid-19 morbidity and mortality [34][35][36][37]. Again, in a pharmacists' intervention study in Saudi Arabia [26], hypertension and diabetes were the most prevalent comorbidities which were diagnosed in 59.5% and 58% of the patients respectively, quite higher compared to 35% and 18.7% obtained in our study. Other pharmacists' intervention studies also showed hypertension, diabetes, and renal impairment as most prevalent in a Covid-19 ward [38].…”
Section: Discussionsupporting
confidence: 91%
“…The mean age of our study is in line with other published literature related to pharmacists' intervention in a Covid-19 scenario. [26]. Other pharmacists' intervention studies in Covid-19 settings had more males than females [27], but other studies were quite similar to this study in terms of their mean age and percentage of females to males [28].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…They also helped with dose adjustment depending on patients' responses, laboratory results, body weight, renal or hepatic impairment, as well as the need for renal replacement therapy, such as hemodialysis or continuous renal replacement therapy (Gurnani et al, 2021;Surapat et al, 2021;Traynor, 2020). One retrospective study identified 470 interventions done by pharmacists to critically ill patients within less than 3 months during the pandemic (Alwhaibi et al, 2021). Most of these interventions pertained to suggesting alternatives to drugs on shortage.…”
Section: Specialized Clinical Pharmacistsmentioning
confidence: 99%